Observation of B+→J/ψ3π+2π− and B+→ψ(2S)π+π+π− decays. - Aaij, R; Adeva, B; Adinolfi, M; Evans, T; Gandini, P; Gruberg Cazon, B; Hadavizadeh, T; Harnew, N; Hill, D; Jalocha, P; John, M; Jurik, N; et al. (Springer, 2017)
The decays B+→J/ψ3π+2π− and B+→ψ(2S)π+π+π− are observed for the first time using a data sample corresponding to an integrated luminosity of 3.0 fb^-1, collected by the LHCb experiment in proton-proton collisions at the centre-of-mass energies of 7 and 8TeV. The branching fractions relative to that of B+→ψ(2S)K+ are measured to be B(B+ → J/ ψ3π+2π−)/B(B+ → ψ (2S)K+) = (1.88±0.17±0.09)×10^−2, B(B+ → ψ (2S)π+π+π−)/B(B+ → ψ (2S)K+) = (3.04±0.50±0.26)×10^−2,where the first uncertainties are statistical and the second are systematic.